High-field/high-frequency EPR of paramagnetic functional centers in Cu2+- and Fe3+-modified polycrystalline Pb[Zr(x)Ti(1-x)]O3 ferroelectrics - Eichel, Rüdiger-A (Magnetic resonance in chemistry : MRC, 2005)
Copyright 2005 John Wiley & Sons, Ltd